Long-term Effect of Islet Transplantation on Glycemic Variability. Issue 5 (May 2018) - Bertuzzi, Federico; De Carlis, Luciano; Marazzi, Mario; Rampoldi, Antonio Gaetano; Bonomo, Matteo; Antonioli, Barbara; Tosca, Marta Cecilia; Galuzzi, Marta; Lauterio, Andrea; Fava, Danila; Dorighet, Patrizia; De Gasperi, Andrea; et al.
Islet transplantation has been reported to restore normoglycemia and the overall metabolic control in type 1 diabetes mellitus (DM). In the most experienced centers, islet transplantation clinical outcome is similar to that of the whole pancreas transplantation. Long-term islet transplantation function remains a very interesting matter worth discussing. A progressive islet function decrease was reported, probably due to islet exhaustion. In 5 islet-transplanted patients with at least 3-yr follow-up and still insulin independent, their glycemic control was characterized by a blinded retrospective continuous glucose monitoring system (CGMS). Islet transplantation restored glycemic control and glucose variability. Data were compared with patients in the waiting list. All the parameters of glycemic variability tested had improved significantly in patients who had islet transplantation compared with those patients who were on the waiting list. In conclusion, islet transplantation is able to maintain a proper glucose control and normalize glycemic variability in selected patients. A blinded retrospective CGMS is a useful method to characterize glucose homeostasis deeply in vivo in islet-transplanted patients.